2008
DOI: 10.2166/wst.2008.548
|View full text |Cite
|
Sign up to set email alerts
|

Ozone disinfection with the HiPOX™ reactor: streamlining an “old technology” for wastewater reuse

Abstract: Although ozone disinfection is a well established technology for drinking water treatment, ozone disinfection mechanisms in wastewater are not well understood such that, historically, ozone wastewater disinfection has not been a feasible technology to implement. The HiPOx system is an ozone-based pressurized in-vessel system that can be used either as an advanced oxidation reactor or as a highly efficient ozone dissolution system. The pilot-scale HiPOx system was temporarily installed at the Dublin San Ramon S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…MS2 phage was less resistant than literature values (Finch and Fairbairn, 1991;Shin and Sobsey, 2003;Tanner et al, 2004;Ishida et al, 2008). E. coli and most bacteriophages showed similar resistance, while PRD-1 and FX174 were slightly more resistant than the other surrogates at low Ct values.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…MS2 phage was less resistant than literature values (Finch and Fairbairn, 1991;Shin and Sobsey, 2003;Tanner et al, 2004;Ishida et al, 2008). E. coli and most bacteriophages showed similar resistance, while PRD-1 and FX174 were slightly more resistant than the other surrogates at low Ct values.…”
Section: Resultsmentioning
confidence: 65%
“…They concluded that a 5 mg/L transferred ozone dose (equivalent to a Ct = 0.5 (mg/L)-min) was capable of achieving a 6-log virus inactivation credit. Ishida et al (2008) reported that a transferred ozone dose of 3-5 mg/L was sufficient to achieve 6.5-log inactivation of coliphage MS2 with contact times above 10 s in microfiltered effluent. In media-filtered effluent, a transferred ozone dose of greater than 7 mg/L with a contact time over 10 s was required to achieve the same level of inactivation.…”
Section: Inactivation Of Pathogenic Viruses By Ozonementioning
confidence: 99%
“…Thus, like UV treatment, ozone treatment was insufficient to meet California Title 22 requirements for virus removal. Moreover, poliovirus has been shown to be more resistant to ozone than MS2 [30], and thus, a 6.5-log inactivation of MS2 is required via ozonation to meet California standards [31]. Ishida et al [31] successfully demonstrated a 6.5-log reduction of MS2 with an applied ozone dose of 5-7 mg/L for filtered graywater.…”
Section: Disinfection Of Pathogensmentioning
confidence: 99%
“…Moreover, poliovirus has been shown to be more resistant to ozone than MS2 [30], and thus, a 6.5-log inactivation of MS2 is required via ozonation to meet California standards [31]. Ishida et al [31] successfully demonstrated a 6.5-log reduction of MS2 with an applied ozone dose of 5-7 mg/L for filtered graywater. However, for graywater with high organic content, treatment modifications clearly would be needed to achieve the required virus inactivation.…”
Section: Disinfection Of Pathogensmentioning
confidence: 99%
“…Its broad applicability, such as its use in evaluation of the efficacy of systems to treat wastewater [4][5][6][7][8][9][10][11][12] and evaluation of ground-water sources [13] has resulted in MS2 testing becoming an integral component of multiple standards, including the National Sanitation Foundation's (NSF) P248 protocol for testing Microbiological Water Purifiers for use in Emergency Military Operations [14] and the EPA/NSF Environmental Technology Verification Program (ETV) Protocol for equipment verification testing for inactivation of microbiological contaminants [15]. The World Health Organization (WHO) also recommends MS2 and somatic coliphage as surrogates for pathogenic viruses in testing and evaluating household water treatment devices [16].…”
Section: Introductionmentioning
confidence: 99%